DangER: protein ovERload. Targeting protein degradation to treat myeloma - Aronson, L. I.; Davies, F. E. (Haematologica (Roma), 2012)
Myeloma is a malignancy of the antibody-producing plasma cells and, as such, these cells synthesize large quantities of unfolded or misfolded immunoglobulin. The build-up of excess protein triggers a number of downstream signal transduction cascades, including endoplasmic reticulum stress and autophagy. As a result, myeloma cells are uniquely reliant on these and other protein handling pathways for their survival. Strategies aimed at targeting this vulnerability have proved successful with the proteasome inhibitor, bortezomib, already licensed for clinical use. In addition to the proteasome, various other points within the protein handling pathways are also the subject of drug discovery projects, with some already progressing into clinical trials. These include compounds directed against heat shock proteins, the unfolded protein response and pathways both upstream and downstream of the proteasome. More recently, the role of autophagy has been recognized in myeloma. In this review, we discuss the various pathways used by myeloma cells for survival, with particular emphasis on the emerging role and conundrum of autophagy, as well as highlighting pre-clinical research on novel inhibitors targeting protein handling pathways.